Psychometric Properties of the Cornell Scale for Depression in Dementia in Elderly Individuals with Dementia in Isfahan, Iran - Nasrin Masaeli; Gholam Reza Kheirabadi; Anahita Khedri; Mohammad Reza Maracy; Victoria Omranifard (Vesnu Publications, 2017)
Introduction: Depression is the second most prevalent psychological disorder in the elderly. This study was designed to evaluate the psychometric properties of the Cornell Scale for Depression in Dementia (CSDD) in the elderly population afflicted with dementia in Isfahan, Iran. Materials and Methods: This psychometric study was performed on 110 elderly individuals who were selected randomly from among individuals who were referred to the elderly clinic of Isfahan and were diagnosed as a case of dementia based on the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV-TR) criteria. All participants completed the CSDD, Mini-Mental State Examination (MMSE), and Geriatric Depression Scale (GDS). The collected data were analyzed descriptive statistics, Cronbach's alpha, factor analysis, and the Pearson correlation coefficient in SPSS software. Results: Total scale reliability coefficient was 0.85 and the reliability of the factors of depression, psychotic depressive symptoms, sleep disorders, somatic symptoms, and anxiety was 0.77, 0.63, 0.79, 0.62, and 0.47, respectively. The correlation coefficient of GDS and MMSE with total scale of CSDD was obtained as 0.47 (P < 0.01) and 0.35 (P < 0.10), respectively, using the Pearson coefficient. Exploratory factor analysis showed that the 5 abovementioned extracted factors had common variance of 58.72%. Conclusion: The Persian version of CSDD contained acceptable psychometric properties in this sample of Iranian elderly individuals with dementia.